Perkhidmatan kesihatan pekerja di Jabatan Kesihatan Negeri Terengganu - Azmi H.,; Mohd Kamil H.,; Abdul Razak K., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2000)
Occupational Health Service in Terengganu Health Department started in 1996. It initially started with occupational health clinic activities in Kemaman. On 17th Jun 1997 Occupational Health Unit was formed in the State Health Department. The aim was to develop the state occupational health activities in districts and hospitals as a whole. It was headed by a State Health Officer (Occupational Medicine Doctor) and assisted by Health Inspectors. In spite of insufficient staff and heavy work load, we managed to develop two occupational health clinic in the health districts of Kemaman and Kuala Terengganu. Beside the clinic, all Hospitals and District Health Offices in Terengganu had formed safety committee as required by OSHA 1994. Training of the staffs was done to enhance the knowledge and skill in occupational health and safety. Beside medical surveillance on the health worker, epidemiology surveillance were done on occupational disease/accident and pesticide chemical poisoning were. Since then, two posts of occupational health officer in The Health District of Kemaman and Kuala Terengganu and one post of occupational staff nurse in Kemaman Health Office were approved in 1998. Application of information technology in occupational health activities in the state are also being considered.